An investigation of the impact of the Global Gag Rule on women's sexual and reproductive health outcomes in Uganda: a difference-in-differences analysis. Issue 1 (31st December 2022) - Giorgio, Margaret; Makumbi, Fredrick; Kibira, Simon P. S.; Bell, Suzanne O.; Chiu, Doris W.; Firestein, Lauren; Sully, Elizabeth
Abstract: In 2017, the Trump administration reinstated the Global Gag Rule (GGR), making non-U.S. non-governmental organisations ineligible for US government global health assistance if they provide access to or information about abortion. Little is known about the impact of the Trump administration's GGR on women's outcomes. Data for this analysis come from a panel of women surveyed in 2018 and 2019 in Uganda ( n = 2755). We also used data from meetings with key stakeholders to create a detailed measure of exposure to the GGR within Uganda, classifying districts as more or less exposed to the GGR. Multivariable regression models were used to assess changes in contraceptive use, all births, unplanned births, and abortion from before to during implementation of the GGR. Difference-in-differences (DID) estimates were determined by calculating predicted probabilities from interaction terms for exposure/survey round. Descriptive analyses showed long-acting reversible contraceptive use increased more rapidly among women in less exposed districts after GGR implementation. DID estimates for contraceptive use were small. We observed a DID estimate of 3.5 (95% CI −0.9, 7.9) for all births and 2.9 (95% CI −0.2, 6.0) for unplanned births for women in more exposed districts during the period the policy was in effect. Our results suggest that the GGR may have attenuated Uganda's recent progress in improving SRHR outcomes, with women in less exposed districts continuing to benefit from this progress, while previously increasing trends for women in more exposed districts levelled off. Although the GGR was rescinded in January 2021, the impact of these disruptions may be felt for years to come.